1902-03 Va. Acts & Resolutions 331-32, Extra Session, ch. 227, §2070a. - (:unkn) unknown (My University, 1903)
It shall be unlawful for any person to shoot at, kill or capture any wild water fowl or wild turkey at any time during the night in this State. . . or to shoot at any game on land or water in this State with a gun larger than an eight bore. . . The possession of any of said guns, sneak boats, nets, traps, reflectors, or other unlawful appliances shall be prima facie evidence of the guilt of the person in whose possession they are found.
Keywords: HUNTING REGULATION